A Cav3.2/Stac1 molecular complex controls T-type channel expression at the plasma membrane. Issue 5 (2nd September 2016) - Rzhepetskyy, Yuriy; Lazniewska, Joanna; Proft, Juliane; Campiglio, Marta; Flucher, Bernhard E.; Weiss, Norbert
ABSTRACT: Low-voltage-activated T-type calcium channels are essential contributors to neuronal physiology where they play complex yet fundamentally important roles in shaping intrinsic excitability of nerve cells and neurotransmission. Aberrant neuronal excitability caused by alteration of T-type channel expression has been linked to a number of neuronal disorders including epilepsy, sleep disturbance, autism, and painful chronic neuropathy. Hence, there is increased interest in identifying the cellular mechanisms and actors that underlie the trafficking of T-type channels in normal and pathological conditions. In the present study, we assessed the ability of Stac adaptor proteins to associate with and modulate surface expression of T-type channels. We report the existence of a Cav 3.2/Stac1 molecular complex that relies on the binding of Stac1 to the amino-terminal region of the channel. This interaction potently modulates expression of the channel protein at the cell surface resulting in an increased T-type conductance. Altogether, our data establish Stac1 as an important modulator of T-type channel expression and provide new insights into the molecular mechanisms underlying the trafficking of T-type channels to the plasma membrane.